Corporate Social-Environmental Responsibility as an Attraction and Retention Factor for Young Professionals - Marcos Cohen; Flávia de Souza Costa Neves Cavazotte; Taissa Mattos da Costa; Karina Cordeiro Silva Ferreira (BBR: Brazilian Business Review, 2017)
This research investigates if company social-environmental responsibility (SER) is an attraction and retention factor for young professionals in two studies. The first study, an experiment, investigates whether such practices influence the attraction exerted by the company as a prospect employer among undergraduate students, considering different wage and professional development conditions. The second study, a survey, investigates the impact of company SER on voluntary turnover among trainees, controlling for individual differences and satisfaction with income, growth and interests. The results suggest that SER is an important element in the attractiveness exercised by companies as they recruit young professionals, and in the retention of trainees, since it is statistically associated with the likelihood of them leaving their companies after disputed selection processes and expensive training programs.